The Mechanism of Sevoflurane Preconditioning-Induced Protections against Small Intestinal Ischemia Reperfusion Injury Is Independent of Mast Cell in Rats - Gan, Xiaoliang; Su, Guangjie; Zhao, Weicheng; Huang, Pinjie; Luo, Gangjian; Hei, Ziqing (Mediators of Inflammation, 2013)
The study aimed to investigate whether sevoflurane preconditioning can protect against small intestinal ischemia reperfusion (IIR) injury and to explore whether mast cell (MC) is involved in the protections provided by sevoflurane preconditioning. Sprague-Dawley rats exposed to sevoflurane or treated with MC stabilizer cromolyn sodium (CS) were subjected to 75-minute superior mesenteric artery occlusion followed by 2-hour reperfusion in the presence or absence of MC degranulator compound 48/80 (CP). Small intestinal ischemia reperfusion resulted in severe intestinal injury as demonstrated by significant elevations in intestinal injury scores and p47phox and gp91phox, ICAM-1 protein expressions and malondialdehyde and IL-6 contents, and MPO activities as well as significant reductions in SOD activities, accompanied with concomitant increases in mast cell degranulation evidenced by significant increases in MC counts, tryptase expression, and β-hexosaminidase concentrations, and those alterations were further upregulated in the presence of CP. Sevoflurane preconditioning dramatically attenuated the previous IIR-induced alterations except MC counts, tryptase, and β-hexosaminidase which were significantly reduced by CS treatment. Furthermore, CP exacerbated IIR injury was abrogated by CS but not by sevoflurane preconditioning. The data collectively indicate that sevoflurane preconditioning confers protections against IIR injury, and MC is not involved in the protective process.